Exploring the effect of foreshores on dike breach development via a mid-scale experiment - van den Berg, Mario; Labeur, Robert J.; Aarninkhof, Stefan G.J.; Visser, Paul J. (Journal of Coastal and Hydraulic Structures, 2025)
Coastal and fluvial flood defences currently rely primarily on existing (grey) infrastructure such as dikes. However, coastal flood risk is expected to increase substantially in the near future. This requires ever increasing efforts to strengthen dikes. To aid these conventional methods, Nature-based Solutions (NbS) are increasingly proposed, such as coastal wetlands. Coastal wetlands have many ecological benefits, but also aid flood protection, especially tidal marshes. Tidal marshes protect the dikes behind them through wave attenuation and reduce flood damage if the dike is breached. Meanwhile, flood risk assessment relies on dike breach modelling to estimate the breach discharges for inundation simulations. Yet, how these foreshores (e.g., tidal marsh) affect dike breach development is largely unknown. For this reason, we experimentally explore how different foreshores affect the dike breaching process. In this study we performed a series of breach tests with a 1.5-1.9 m high model sand-dike with and without a foreshore. We tested two types of foreshores, an erodible sand and low-erodible clay layer, acting as proxies for a sandy beach and unvegetated tidal marsh. Because dike breach flow closely resembles weir flow, the standard weir equation applies, which is also frequently used in breach discharge models. The observed foreshore effects are qualitatively evaluated using this weir equation. Depending on foreshore stability, we find that foreshores affect breach hydrodynamics which alters the weir shape, leading to reduced breach width growth and ultimately limits the specific discharge.